2020
DOI: 10.1210/clinem/dgaa069
|View full text |Cite
|
Sign up to set email alerts
|

Forty-One Individuals With Mutations in the AVP-NPII Gene Associated With Familial Neurohypophyseal Diabetes Insipidus

Abstract: Context Familial neurohypophyseal diabetes insipidus is a rare disease produced by a deficiency in the secretion of antidiuretic hormone and is caused by mutations in the arginine vasopressin gene. Objective Clinical, biochemical, and genetic characterization of a group of patients clinically diagnosed with familial neurohypophyseal diabetes insipidus, 1 of the largest cohorts of patients with protein neurophysin II (AVP-NPII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Most of the variants of this gene are situated in the NPII gene, with seven variants detected [9]. As has been described, seven intrachain disulfide bonds are formed in NPII, which may be essential for stabilizing the protein.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most of the variants of this gene are situated in the NPII gene, with seven variants detected [9]. As has been described, seven intrachain disulfide bonds are formed in NPII, which may be essential for stabilizing the protein.…”
Section: Discussionmentioning
confidence: 88%
“…First, there may be a decline in the number of binding sites and activity of endopeptidase responsible for the cleavage of ADH [8]. Second, there may be a change in the pattern of polymerization of NPII and its binding of ADH, which in turn may result in a specific enzymatic degradation of the hormone [9,10]. Both of these effects can lead to deficiency in the amount of available ADH.…”
mentioning
confidence: 99%
“…Previous studies have found a bioavailability of 10-20 times higher with the nasal administration than with the oral form [5,9,[14][15][16]. Based on previous practice, we decided to multiply the dose with 20 when converting nasal dose to oral dose, and multiply with 1.67 when converting sublingual dose to oral dose [3,7]. The "desmopressin dose requirement" was calculated as the sum of all desmopressin taken during one day after converting it to the equivalent oral doses.…”
Section: Primary Outcomementioning
confidence: 99%
“…The various etiologies of DI include congenital and acquired causes [1,2]. Most cases of cDI are acquired and may be due to neoplasm, infection, head trauma, hypophysitis, or surgery affecting the pituitary gland with the majority being due to neurosurgery, which may lead to both partial cDI and complete cDI [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The mutation pattern of the AVP gene, initiating the pathogenic cascade of events in adFNDI, determines the accumulation of misfolded (or unfolded) AVP precursor proteins in the ER, causing ER stress and progressive degeneration of vasopressinergic magnocellular neurons [6,7]. A minority of AVP gene variants causing adFNDI, such as the common G to A transition in position 55 of the coding DNA reference sequence (c.55G>A), also known as g.279G>A, according to previous nomenclature based on genomic location, are predicted to affect amino acid residues close to the SP cleavage site [8,9], resulting in abnormal post-translational processing and intracellular trafficking of preproAVP and proAVP [10]. Generally, these SP mutations cause a gradual decline in neurohypophyseal secretion of AVP during the first years of life, although wide variations in the age of onset and severity of symptoms have been reported [10], and are speculated to be consequences of environmental factors and individual abilities of scavenging the retained pathogenic aggregates of AVP precursors [6,11,12].…”
Section: Introductionmentioning
confidence: 99%